Stabilizace akromioklavikulární luxace tahovou cerkláží ve srovnání s jedním Kirschnerovým drátem doplněným kličkou z částečně vstřebatelného materiálu – nerandomizovaná retrospektivní studie - Trávník, J; Kovařík, J; Pavlacký, T; Veselý, R; Pink, T; Paša, L (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2019)
PURPOSE OF THE STUDY Acromioclavicular joint dislocations (AC) represent one of the most frequent injury to the shoulder gridle. Low grade injuries type Rockwood I-II are treated non-operatively. Whereas high grade injuries type Rockwood III-VI are usually treated operatively. At present a wide spectrum of surgical techniques is used: Bosworth screw, hook plate, pinning and tension banding, PDS-sling. In our study the pinning and tension banding technique and the modified orthocord sling technique were compared. The goal of this study was to determine whether there are any clinical and radiological differences between these two techniques. MATERIAL AND METHODS This retrospective non-randomized level 3 evidence study included 58 patients. All of them have sustained a Tossy III AC dislocation. Of the 58 patients, 31 were treated with pinning and tension banding. Modified orthocord (absorbable knitted strand) sling technique (One 2.0-2.5 mm Kirchner wire, orthocord tension banding and coraco-clavicular ligament suture) was used in 27 patients. The same regime was used in postoperative follow up. For the clinical assessment the ASES and Constant score were used. The presence of calcification, degenerative changes, clavicular dislocation were assessed during the X-ray follow-ups. RESULTS The mean treatment time was 18.7 ± 4.9 weeks in the pinning and tension band group (Group A), whereas 15.8 ± 2.8 weeks in the modified orthocord sling technique (Group B). There was a significantly shorter period of healing in Group B. There were no statistically significant differences in the K wire removal time (Group A: 12.6 ± 3.7, Group B: 11.9 ± 3.2). No significant difference was observed between Group A and Group B on the ASES score (Group A: 95 ± 5.8, Group B: 98 ± 3.1) and on the Constant score (Group A: 97.7 ± 3.2, Group B: 97.9 ± 2.9). There were significant differences in both groups between the injured and non-injured shoulder on the Constant score. The mean secondary clavicular dislocation in Group A was 7.2 ± 1.8 mm in the operated shoulder and 4.8 ± 2.0 mm in the non-operated shoulder. The secondary dislocation in Group B was 7.5 ± 2.0 mm in the injured shoulder and 4.2 ± 1.2 mm in the non-injured shoulder. There was a significant difference between the injured and the non-injured shoulder in both groups. Calcification in coraco-clavicular ligament was observed in 15 (48.4%) Group A cases and in 13 (48.1%) Group B cases. Secondary AC joint arthrosis was observed in 8 (25.8%) Group A cases and in 1 (3.7%) Group B case. DISCUSSION No significant difference in clinical outcomes between both the surgical techniques was found. These results are comparable with other, recently published studies. On the other hand, we observed a significantly decreased treatment time with the modified orthocord sling technique. One, centrically inserted Kirschner wire, might better tolerate small rotation movements in the AC joint. Secondary clavicular dislocation, Kirschner wire dislocations and wound complications were similar in both groups and comparable to other, recently published studies. CONCLUSIONS Even though the tension banding and orthocord modified sling rank among the oldest and the cheapest techniques available for AC dislocation treatment, their results are comparable with modern and costly techniques. The orthocord modified sling technique has an advantage of fast and cheap material extraction in outpatient conditions. Key words: AC dislocation, acromioclavicular joint dislocation, orthocord sling, tension banding, AC disruption, acromioclavicular joint disruption.
Keywords: dislokace kloubu; Shoulder Dislocation; akromioklavikulární kloub; retrospektivní studie; Immobilization; Acromioclavicular Joint; Humans; imobilizace; výsledek terapie; lidé; luxace ramenního kloubu; Retrospective Studies; Treatment Outcome; Joint Dislocations